Comparative phylogeography and phylogenetic relationships of the four-striped mouse genus, Rhabdomys, and the ectoparasitic sucking louse, Polyplax arvicanthis - Du Toit, Nina (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.